The Value of Negotiating Cost-Based Transfer Prices - Anne Chwolka; Jan Thomas Martini; Dirk Simons (BuR - Business Research, 2010)
This paper analyzes the potential of one-step transfer prices based on either variable or full costs for coordinating decentralized production and quality-improving investment decisions. Transfer prices based on variable costs fail to induce investments on the upstream stage. In contrast, transfer prices based on full costs provide strong investment incentives for the upstream divisions. However, they fail to coordinate the investment decisions. We show that negotiations prevent such coordination failure. In particular, we find that the firm benefits from a higher degree of decentralization so that total profit increases in the number of parameters being subject to negotiations.
urn:nbn:de:0009-20-26801
Keywords: 650; centralized management; decentralized management; investment; product differentiation; transfer pricing; negotiations; Verrechnungspreis; Dezentrale Organisation; Produktdifferenzierung; Investitionsrisiko; Verhandlungen